The level of Internet access and ICT training for health information professionals in sub-Saharan Africa (2008)
Information and Communication Technologies (ICTs) are important tools for development. Despite its significant growth on a global scale, Internet access is limited in sub-Saharan Africa (SSA). Few studies have explored Internet access, use of electronic resources and ICT training among health information professionals in Africa. The study assessed Internet access, use of electronic resources and ICT training among health information professionals in SSA. A 26-item self-administered questionnaire in English and French was used for data collection. The questionnaire was completed by health information professionals from five Listservs and delegates at the 10th biannual Congress of the Association of Health Information and Libraries in Africa (AHILA). A total of 121 respondents participated in the study and, of those, 68% lived in their countries’ capital. The majority (85.1%) had Internet access at work and 40.8% used cybercafes as alternative access points. Slightly less than two-thirds (61.2%) first learned to use ICT through self-teaching, whilst 70.2% had not received any formal training in the previous year. Eighty-eight per cent of respondents required further ICT training. In SSA, freely available digital information resources are underutilized by health information professionals. ICT training is recommended to optimize use of digital resources. To harness these resources, intergovernmental and non-governmental organizations must play a key role.